RAIDE: A Tool for Assertion Roulette and Duplicate Assert Identification and Refactoring - Santana, Railana; Martins, Luana; Rocha, Larissa; Virgínio, Tássio; Cruz, Adriana; Costa, Heitor; Machado, Ivan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Test smells are fragments of code that can affect the comprehensibility and the maintainability of the test code. Preventing, detecting, and correcting test smells are tasks that may require a lot of effort, and might not scale to large-sized projects when carried out manually. Currently, there are many tools available to support test smells detection. However, they usually do not provide neither a user-friendly interface nor automated support for refactoring the test code to remove test smells. In this work, we propose RAIDE, an open-source and IDE-integrated tool. RAIDE assists testers with an environment for automated detection of lines of code affected by test smells, as well as a semi-automated refactoring for Java projects using the JUnit framework.